High animal protein diet and gut microbiota in human health. Issue 22 (22nd July 2022) - Cai, Jie; Chen, Zhongxu; Wu, Wei; Lin, Qinlu; Liang, Ying
Abstract: The role of the intestinal flora in health and disease has become a research hotspot. Compared with carbohydrates and fats, proteins are metabolized primarily by microbial fermentation in the intestine. The production of protein fermentation products and metabolites depends on the composition, diversity, and metabolism of the gut microbiota. Several protein fermentation products, including indoles, phenols, polyamines, hydrogen sulfide (H2 S), amines, and carnitine, are toxic. This study analyzes the relationship between high-protein diets (HPDs), the intestinal microbiota, and human health and disease. Long-term HPDs increase the risk of intestinal diseases, type 2 diabetes (T2DM), obesity, central nervous system (CNS) diseases, and cardiovascular diseases (CVD) by producing toxic metabolites in the colon, including amines, H2 S, and ammonia. Short-term HPDs have little effect on the metabolism of healthy individuals under 65 years old. However, meeting the protein requirements of individuals over 65 years old using HPDs is more challenging. The adverse effects of HPDs on athletes are minimal. Natural compounds (plant extracts, whose main constituents are polysaccharides and polyphenols), prebiotics, probiotics, and regular physical exercise improve gut dysbiosis and reduce disease risk.